Peran Ideologi Pancasila Sebagai Dasar Negara Dalam Kehidupan Mahasiswa - TANDING NIKEN SUKASIH (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2023)
ABSTRACT Indonesia is one of the plural nations, Indonesia has a lot of diversity in each region, both cultural diversity, ethnicity, race, religion and language. Pancasila itself is a symbol of national unification that is used as a basis for organizing the administration of the state and regulating the entire order of life of its people. This article is made in line with the rapid development of technology and science which certainly affects the erosion of the main values of Pancasila as a guide in life. The understanding and application of the noble values of Pancasila ideology that tend to be lacking in the lives of students make them often behave contrary to legal regulations and norms that apply in Indonesia. The method in the study of this article is mixed methods. Data were collected through direct observation techniques, interviews and also obtained from literature studies on relevant sources. The goal to be achieved is to find out the extent to which the average student understands the ideology of Pancasila and how to maintain the ideology of Pancasila as a basis for behavior.